Atlantic Green Chemicals : bio-glycol plants : business plan - Arnfinnur Teitur Ottesen 1977- (2012)
Atlantic Green Chemicals (AGC) has made a license agreement with its sister company Icelandic Process Development (IPD) about building and managing three Glycerin to Glycols Plants based on IPD patent that transforms glycerin (a byproduct from bio-diesel production) to Propylene Glycol (PG) using steam and hydrogen. PG has till now been made from fossil fuel in oil refineries. PG is in high demand as de-icing fluid for airplanes, polyester resins, detergents, food, drugs and cosmetics. As fossil fuel product prices of PG has to large extent followed oil prices, while glycerin as a byproduct of bio-diesel has due to oversupply became inexpensive, thus creating very lucrative spread. AGC has located three site locations were condition are favorable for building such plants, these are Helguvik in Iceland, Delfizij in Holland and Fray Bentos in Uruguay. Moreover, the environmentally friendly production process is likely to give this kind of PG a preference in the market place or allow for some kinds of subsidies or governmental grants especially in the European Union. The purpose of this report is to create a detailed and formulized business plan for Atlantic Green Chemicals, and valuate these three locations based on known and tested business techniques and researched facts and figures on Capital Expenditures (CAPEX) and Operational Expenditures (OPEX) of these proposed plants. The research question here is to evaluate how appealing AGC is as an investment case offered for variety of investors in Iceland as well as internationally.